Developing criteria and designing a tool for evaluating textbooks of teaching Arabic to non-native speakers : an analysis of Malaysian experts' views - Chik, Abdul Rahman (s.n, 2013)
This study aims to develop comprehensive criteria for evaluating Arabic Textbooks in teaching Arabic as a second language. To decide what criteria were important, a review of related literature was conducted by taking into consideration the criteria and studies conducted by Rushdie Toeima, Harun Husaini, Jaya Karan, Skierso, ACTFL and Malaysia Ministry of Education. A draf of criteria were developed and submitted to the experts of this area for technical review. Based on their comments, the finalized criteria have been created and a tool for evaluating textbooks in teaching Arabic to non-native speakers was proposed